PENGEMBANGAN MATERI MANAJEMEN DIRI - Surtia Mustika; Rosmawati '; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims at drafting material about self management needed for junior high school students in terms of the clarity of the material , the material systematics , image support , renewal of the material , and completeness of the materials and support vidio / game . Before the researchers gave the material to the students , the researchers first demonstrated the results of his material to the supervisor I and II lecturers , teachers on counseling where researchers do research as much as 2 people . After much pass a revision with the suggestions by experts subsequent researchers provide self management material is 4x meeting . Then, after the researchers gave the students teaching materials such materials provide an assessment of the self management of a given material. Of the value given by experts and students of the obtained results of calculations for clarity aspects of material gain values including very clear category with a score of 4.43 , for the systematic aspects of material gain values including systematic category with a score of 3,80 , to aspects of image support received grades 4.47 which included a very good category , for the aspects of renewal of the material received grades 4.05 which included a new category , and for aspects of the completeness of the materials obtained a value of 4.58 which included a very complete category , and to support the games / vidio scored 4.41 which includes very support category , whereas for all aspects of the material assessment showed that the materials developed already meet the criteria are expected to obtain a value of 4.29 which included a very good category .Keywords : Material development , self management